Engfi Gate: An Indoor Guidance System using Marker-based Cyber-Physical Augmented-Reality - Hanas Subakti; Herman Tolle; Muhammad Aswin (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A guidance system is needed when freshmen explore their new building environment. With the advancements of mobile technologies, a guidance system using mobile computing devices such as mobile phones or tablets could aid freshmen in locating the desired destination with ease. The proposed system consists of three main subsystems: the marker-based cyber-physical interaction (CPI) system, the indoor positioning (IP) system, and the augmented-reality (AR) system. With the help of visible markers and invisible markers, the CPI system allows the users to do interactions between the physical and cyber environments; the IP system produces accurate user position information; the AR system provides the users with good user experiences. An Android application, named Engfi Gate, is developed to realize the system design in the test environment. This paper also shows the comparisons of the proposed system with other related systems. Furthermore, the design architecture of Engfi Gate system can be used in other location-based applications.